Streptococcus suis disease investigation in an ordination ceremony Dan Khun Thot District, Nakhon Ratchasima Province, between 28 March - 11 April 2021 - Sukto, Chayaphon; Kaewsang, Onnicha (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2023)
On 1st April 2021, the Provincial Public Health Office, Nakhon Ratchasima was notified of two cases of confirmed Streptococcus suis (S. suis) infection. They had a history of consuming foods in the ordination ceremony at Dan Khun Thot District, Nakhon Ratchasima Province. The investigation was provided to confirm the diagnosis, find the source of the disease, and impose measures for the prevention and control of disease outbreaks. A descriptive study was conducted, and S. suis patients treated at Dan Khun Thot Hospital were investigated. Active case finding in communities by using the definition of S. suis case was done. Laboratory testing was performed by collecting blood or cerebrospinal fluid for bacterial culture. Serotype identification was conducted by randomization. An analytical epidemiology and environmental study were performed to determine the cause of the disease focused on contamination and cooking processes. The results found that 88 of 241 participants in the ordination ceremony had symptoms, and 20 participants were confirmed cases. One hundred percent had a fever, followed by headache (88.64%), myalgia (62.50%), and diarrhea (30.68%). A point common source outbreak was identified. Streptococcus suis serotype 2 was detected. The study found that eating undercooked food from raw pork, for example, Larb, and drinking alcoholic beverages increased the risk of severe disease. In conclusion, the streptococcus suis outbreak was found at the ordination ceremony in Dan Khun Thot district between March 28 - April 11, 2021. A total of 88 cases were definition cases, 20 confirmed cases, and died 2 cases. The mortality rate was 2.34 percent. The cause of infection might be due to raw pork contamination with S. suis in the process of cooking in this ceremony.